Clusters of alcohol and drug use and other health-risk behaviors among Thai secondary school students: a latent class analysis - Sawitri Assanangkornchai; Jing Li; Edward McNeil; Darika Saingam (BMC, 2018)
Abstract Background Alcohol and drug use and other health-risk behaviors tend to cluster together among adolescents and contribute a large amount of harm to both themselves and to others. This paper aims to characterize secondary school students based on their clusters of health-risk behaviors and identify factors determining class membership to these behavior-clusters. Methods Data from a national school survey was used to identify clusters of alcohol and drug use and other health-risk behaviors among secondary school students aged 12-15 years using a latent class regression model. A multinomial logistic regression model was used to identify predictors of the cluster membership. Results A total of 25,566 students were included in the analysis, of which 88% were classified as having low-risk behaviors reporting only moderate alcohol use; 11% as having moderate-risk behaviors, such as driving under the influence of alcohol, fighting, carrying a weapon, and alcohol and tobacco use; and 0.6% as having high-risk behaviors, such as use of illicit drugs, particularly kratom and cannabis. Males, older students, those with a poor school performance, not living with parents, drug use by family members and peers, and having a low level of perceived disdain from their friends if they used drugs were significant risk factors for being in the moderate- and high-risk behavior classes. Conclusions Alcohol, tobacco and drug use, as well as other health-risk behaviors such as fighting, are clustered in Thai secondary school students. This result highlights the importance of comprehensive prevention and education strategies, particularly for moderate to high-risk groups.